(untitled) (Revista Brasileira de Contabilidade e Gestão, 2019)
The present research aims to identify the strategies of sustainable management and the export performance of a company of plastic transformers. The transformation of plastic material is the third generation of the petrochemical production chain and is responsible for producing packaging, parts and utensils for almost all productive segments of the economy. In methodological terms a qualitative research of descriptive approach was developed. The collection and analysis of data on sustainable management strategies were based on the models of Placet, Anderson, Fowler (2005) and Lacy et al (2010). The export performance was analyzed from the studies of Papadopoulos and Martín (2010). The main results revealed that sustainability is fully integrated with the company’s strategy, yet it has a still incipient export performance.